Opening an Online Wadiah Savings Account in Sharia Banking - Hardiati, Neni; F, Fitriani; Nugroho, Wahyu (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The development of the all-digital era today saving can be through online wadiah savings are savings issued by Islamic banks, where this savings carry the concept of sharia based on the principle of wadiah. The concept of wadiah itself has developed since the time of the Prophet. This article uses qualitative research methods with literature studies sourced from previous scientific works and through Islamic banking websites. Views and opinions on the concept of wadiah were introduced by maliki, Hanafi and syafei. Wadiah savings itself are divided into two types according to their use, namely the trust wadiah contract and the dhamanah wadiah contract. For the terms and conditions in opening wadiah savings at Sharia Banks, you must follow the principles and conditions of the wadiah contract.